Assessing the immunomodulatory role of heteroglycan in a tumor spheroid and macrophage co-culture model system. (20th August 2015) - Devi, K. Sanjana P.; Mishra, Debasish; Roy, Bibhas; Ghosh, Sudip K.; Maiti, Tapas K.
Highlights: A tumor spheroid and macrophage co-culture system was developed. Immune stimulating functions of heteroglycan was tested in such co-culture models. Macrophage mediated tumor cytotoxicity was observed after heteroglycan treatment. Heteroglycan exposure oriented the macrophages into tumor-inhibiting type. Abstract: The therapeutic benefits of glycans have garnered much attention over the last few decades with most studies being reported in 2D cultures or in animal models. The present work is therefore aimed to assess the effects of an immunomodulatory heteroglycan in a 3D milieu. Briefly, HT29 tumor spheroids were incubated with THP-1 macrophages at 1:1 ratio in a culture medium supplemented with immune stimulants such as heteroglycans or LPS. Spheroidal distortion, migration of tumor cells from the periphery of the spheroids and 46% of higher macrophage invasiveness was noted in heteroglycan-treated co-cultures with respect to control cultures. Histological sections of the treated co-cultures revealed the presence of high apoptotic tumor cells in the spheroidal periphery. CD11c and CD68 staining further suggested the predominance of macrophages in the vicinity of the apoptotic tumor cells. Such an in vitro created tissue system may thereby confirm the effectiveness of heteroglycan in activating the immune cells to exhibit tumor cytotoxic properties.